CONTEMPORARY LANDSCAPE IN TRADITIONAL GOND ART: पारम्परिक गोंड कला में समकालीन परिदृश्य - Panwar, Apeksha; Rani, Archana (International Journal of Research -GRANTHAALAYAH, 2021)
English: Indian Folk art mainly depicts social and cultural aspects of trible society. Gond Painting is developed by Gond Community which is a large trible community in India and hence named after the same. “This art is quite famous in central India. Traditionally Gond Art were painted on walls and floors during weddings and on auspicious occasions. With time the art witnessed developments and now it is seen on textile, canvas, clothes, articles and valuable artifacts. Last decade witnessed a boom in the popularity of Gond Art. Jangan Singh Shyam who is called the father of Gond Art is one such artist who introduced Gond art at world platform. The presented research paper highlights the initial and contemporary changes which were introduced by Jangan Singh and his descendants Mayank Shyam (Son) and Japani Shyam (Daughter) and famous gond artist Vanket Raman Singh Shyam in their Gond Paintings under the effects of the surroundings with Time. Hindi: भारतीय लोक कलाएँ मुख्यतः आदिवासी समाज के सामाजिक और सांस्कृतिक स्वरूप को दर्शाती है। गोंड चित्रकला भारत के विशाल जनजातीय गोंड समुदाय द्वारा विकसित की गयी है। अतः इस कला को यह नाम गोंड जनजाति से मिला। यह कला मध्य भारत की एक विख्यात कला है। अपने परम्परागत रूप में गोंड चित्र दीवारों और धरातल पर शादी-विवाह और अन्य शुभ अवसरों पर सृजित किये जाते थे। अब समय के साथ उनके माध्यम में परिवर्तन दिखाई देने लगा और ये कैनवास, पेपर, कपड़े, उपयोगी एवं सजावटी वस्तुओं पर भी बनायी जाने लगी है। पिछले एक दशक में इस कला को अत्यधिक प्रसिद्धि प्राप्त हुई है। गोंड कला के पितामह कहे जाने वाले जनगण सिंह श्याम एक ऐसे पहले कलाकार है जिन्होनेगोंड कला को विश्व स्तर पर परिचित कराया। प्रस्तुत शोध पत्र में गोंड कला के प्रणेता श्री जनगण सिंह श्याम और उनकी कला की संरक्षक पीढी पुत्र मयंक श्याम व पुत्री जापानी श्याम तथा प्रसिद्ध चित्रकार वेंकेटरमन सिंह श्याम के चित्रों में पारम्परिक और समसामयिक परिवेश के अनुरूप आये बदलाव के संदर्भ से प्रस्तुत करने का प्रयास किया है।